Pharmacological effects of monoterpene carveol on the neuromuscular system of nematodes and mammals - Stojković, Maja; Todorović, Zoran; Protić, Dragana; Stevanovic, Strahinja; Medić, Dragana; Charvet, Claude L.; Courtot, Elise; Marjanović, Djordje S.; Nedeljković Trailović, Jelena; Trailović, Saša M. (Frontiers in Pharmacology, 2024)
The control of parasitic nematode infections relies mostly on anthelmintics. The potential pharmacotherapeutic application of phytochemicals, in order to overcome parasite resistance and enhance the effect of existing drugs, is becoming increasingly important. The antinematodal effects of carveol was tested on the free-living nematode Caenorhabditis elegans and the neuromuscular preparation of the parasitic nematode Ascaris suum. Carveol caused spastic and geraniol atonic paralysis in C. elegans. In A. suum carveol potentiated contractions induced by acetylcholine (ACh) and this effect was confirmed with two-electrode voltage-clamp electrophysiology on the A. suum nicotinic acetylcholine receptor expressed in Xenopus oocytes. However, potentiating effect of carveol on ACh-induced contractions was partially sensitive to atropine, indicates a dominant nicotine effect but also the involvement of some muscarinic structures. The effects of carveol on the neuromuscular system of mammals are also specific. In micromolar concentrations, carveol acts as a non-competitive ACh antagonist on ileum contractions. Unlike atropine, it does not change the EC50 of ACh but reduces the amplitude of contractions. Carveol caused an increase in Electrical Field Stimulation-evoked contractions of the isolated rat diaphragm, but at higher concentrations it caused an inhibition. Also, carveol neutralized the mecamylamine-induced tetanic fade, indicating a possibly different pre-and post-synaptic action at the neuromuscular junction.